2008
DOI: 10.3168/jds.2007-0905
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Lactation in Dairy Cows: Effect on Milk Production and Mammary Nutrient Supply and Extraction

Abstract: Reports over the past decade have indicated that normal lactational performance can be achieved in genetically superior and high-producing dairy cows, even when the dry period between 2 lactations is omitted. The hypothesis tested in this experiment was that normal lactogenesis I and metabolic function may be achievable in continuously milked high-yielding dairy cows as a result of the genetic selection for lactation performance and hence longevity of mammary epithelial cells. The milk production and mammary n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 27 publications
2
33
1
Order By: Relevance
“…Also, Remond et al (1992) reported a tendency for an increased lactose yield in cows with a DP-60 compared with cows with no dry period. Our data is not consistent with De Feu et al (2009) and Madsen et al (2008) who reported no significant difference between treatments about milk lactose percentage, of course they compared 7-wk or 8-wk dry period with no planned dry periods.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Also, Remond et al (1992) reported a tendency for an increased lactose yield in cows with a DP-60 compared with cows with no dry period. Our data is not consistent with De Feu et al (2009) and Madsen et al (2008) who reported no significant difference between treatments about milk lactose percentage, of course they compared 7-wk or 8-wk dry period with no planned dry periods.…”
Section: Discussioncontrasting
confidence: 99%
“…De Feu et al (2009) compared a standard 8 week dry period with no planned dry period and reported that there were no differences in plasma BHBA concentrations between the dry period treatments from wk −3 to 3 and from week 4 to 12 relative to parturition. Madsen et al (2008) reported similar results regarding plasma BHBA concentrations when cows were assigned either a 7-week dry period or no planned dry period treatments. However, our results with serum BHBA concentrations indicate a 20% increase in DP-60 compared with DP-20 and are in agreement with Andersen et al (2005) who reported that the significant difference in postpartum plasma BHBA concentrations (p = 0.04) between treatments (7-wk dry period vs. no planned dry period).…”
Section: Discussionmentioning
confidence: 59%
“…A high protein value of the milk contributes to a more stable metabolic status of the cow, grades up the delivered milk, and has got a particularly high biological value and nutrient concentration (Lee and Lorenz, 1978;Haug et al, 2007). In search of ways to increase the protein concentration of the milk, and to conserve the metabolism of the cow at the same time, the research regarding the neglecting of the dry period is of major interest (Remond et al, 1992;Remond and Bonnefoy, 1997;Remond et al, 1997a and1997b;Andersen et al, 2005;Fitzgerald et al, 2007;Madsen et al, 2008). The drying-off period is regarded to be the recreational period for the udder: cellular regeneration takes place and the preconditions for a high milk output in the following lactation are set.…”
Section: Introductionmentioning
confidence: 99%
“…The dry period has been proven important for dairy cows. Omitting or shortening the dry period imposes negative effects on mammary health and milk yield in the next lactation [1][3]. The mammary gland does not resume its activity until approximately 2 to 3 weeks before the next parturition, when dramatic changes occur to prepare for profuse milk secretion after parturition.…”
Section: Introductionmentioning
confidence: 99%